WORKER FLOWS ON THE LABOUR MARKET. WHERE DOES THE EMPLOYMENT INFLOW COME FROM? - Gałecka-Burdziak, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The economies are characterized by large flows of workers and job posts. Job flows are connected to job creation and job destruction processes. Worker flows result from job reallocation processes as well as for example from labour force participation decisions. In the article I analyse the importance of worker flows with the emphasis put on the employment inflow structure. In this manner I try to verify whether the unemployed compete for job opportunities with other job seekers. The elements of the derived Markov transition matrix show that the unemployment stock is the most volatile on the Polish labour market and non-negligible fractions of the workers flow to and from inactivity. The unemployed compete for job opportunities and according to economic conditions they constitute (in time span 2000 – 2010) up to 50% of the employment inflow (30% in 2007 – 2008 period). Job-to-job moves also approach two-digit percentages, although on average small share of the employed admit to be looking for another job during the current employment contract. Indications of out-of-labour force search to a large extent depend on data frequency.